2023
DOI: 10.1088/1758-5090/acc35d
|View full text |Cite
|
Sign up to set email alerts
|

A glomerulus chip with spherically twisted cell-laden hollow fibers as glomerular capillary tufts

Abstract: Glomerulus-on-a-chip, as a promising alternative for drug nephrotoxicity evaluation, is attracting increasing attention. For glomerulus-on-a-chip, the more biomimetic the chip is, the more convincing the application of the chip is. In this study, we proposed a hollow fiber-based biomimetic glomerulus chip that can regulate filtration in response to blood pressure and hormone levels. On the chip developed here, bundles of hollow fibers were spherically twisted and embedded in designed Bowman’s capsules to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…[22,42] There was a wide range of concentrations used in this type of assay, and no "gold standard" had been established. Some researchers use higher concentrations, [13,16,67,68] , while others employ the same concentration as we do. [7,15,22] Even some leading experts in this field have adjusted their concentrations over time.…”
Section: Methodsmentioning
confidence: 99%
“…[22,42] There was a wide range of concentrations used in this type of assay, and no "gold standard" had been established. Some researchers use higher concentrations, [13,16,67,68] , while others employ the same concentration as we do. [7,15,22] Even some leading experts in this field have adjusted their concentrations over time.…”
Section: Methodsmentioning
confidence: 99%
“…Inspired by the anatomical structure of glomeruli, Dai et al spherically twisted the hollow fiber bundles and implanted them into Bowman's capsules, followed by successively seeding podocytes and endotheliocytes on the outer and inner side of fibers. 214 Based on the bionic structure design of biomaterials and fluidic culture microenvironment, the glomerulus chip demonstrated the favorable viability and metabolic function of cells, together with the selective barrier and filtration regulation functions of glomerular capillaries.…”
Section: Construction Of Organs-on-chipsmentioning
confidence: 99%
“…In addition, Roye et al constructed glomerular injury model in a glomerulus chip by introducing Adriamycin to destroy the tissue integrality of ECs and podocytes. 214 Employing Pseudorabies virus as an inducible factor in a distal tubule-on-a-chip, Wang et al developed a kidney disease model to study the potential pathogenesis of virus-induced renal dysfunctions. 249 They found that virus infection caused the disorder of Na transporters, injury of reabsorption barrier, transformation of microvilli, as well as abnormalities of serum electrolyte.…”
Section: Applicationsmentioning
confidence: 99%